LIFE AS A GEOGRAPHER IN INDIA - Kapur, Anu. ([S.l.])
1 online resource
Keywords: This is the first book which provides an engaging and insightful narrative on the life of a geographer in India. The author introspects on her own experiences and engagements with the discipline and explores the life and works of twenty-four other geographers from India. The volume documents and acknowledges the commitment of geographers to life, teaching, and the subject of geography. Collectively these provide an insight into the growth and expansion of the discipline in the country. The book offers critical perspectives on the changing disciplinary practices within the field of geography by highlighting the major achievements and teaching methods of geographers. It highlights the diverse interests, themes, and problems in geography which these geographers pursued while also influencing the lives of other researchers and professionals. This book will be of immense interest to students, teachers, and researchers of geography and social anthropology and readers interested in the lives of these influential educators and academicians.